Method for optimizing plastic deformation parameters of Ag / MAX electric contact material
Through the combination of Gleeble simulation processing and three-dimensional thermal processing map, the plastic deformation parameters of Ag/MAX electrical contact materials are optimized, and the problem of random distribution of MAX phase particles is solved, thereby improving material performance and controlling the production process.
Patent Information
- Application Number
- CN202510159137.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-06-03
AI Technical Summary
In the prior art, when preparing Ag/MAX electrical contact materials, MAX phase particles are randomly distributed and have low orientation, resulting in insufficient material performance and relying on empirical parameters to control the plastic deformation process, which has a long R&D cycle and high cost.
Gleeble simulates the stress and strain state and tissue evolution during processing, and uses three-dimensional thermal processing diagrams to divide the safety zone and instability zone of the material during plastic deformation, and optimizes the plastic deformation parameters in combination with the work hardening curve to avoid long-term tests and material waste.
The fine optimization of the plastic deformation parameters of Ag/MAX electrical contact materials is achieved, the experimental process is reduced, the cost is saved, the material production controllability and consistency is improved, and the mechanical and electrical properties of the material are taken into account.
Smart Images

Figure CN120087050A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of plastic forming of metal matrix composites. In particular, it relates to a method for optimizing the plastic deformation parameters of Ag / MAX electrical contact materials. By using a three-dimensional hot processing map and taking into account both mechanical properties and electrical properties, the plastic deformation parameters of Ag-based electrical contact materials are optimized. Background Art
[0002] The Ag / MAX composite material is a MAX-phase particle-reinforced Ag-based electrical contact material, which has excellent electrical conductivity, corrosion resistance, and arc erosion resistance, and has great application potential in low-voltage circuits (for example, used in low-voltage electrical switches, contactors, etc.). Research shows that the directional arrangement of the reinforcement phase can effectively improve the erosion resistance of the arc erosion surface. The Ag / MAX composite material prepared by the traditional powder metallurgy method faces the problems of random distribution of MAX-phase particles and low orientation degree, and at the same time, defects such as pores will inevitably be generated. Such defects can be effectively eliminated through plastic deformation, the distribution of the reinforcement phase can be optimized, and the material properties can be improved. Therefore, optimizing and regulating the microstructure and properties of Ag / MAX electrical contact materials through plastic deformation is an important research direction at present. However, the deformation behavior and microstructure evolution process during plastic deformation have not been fully understood. Especially under high-temperature and high-strain-rate conditions, how the microstructure changes of the material affect the macroscopic properties still needs to be further explored.
[0003] Patent CN109852837A discloses a preparation method of a MAX-phase-reinforced Ag-based electrical contact composite material with a directional arrangement. This patent adopts a method combining powder metallurgy and equal-channel angular pressing (ECAP), which significantly refines the grains of the Ag matrix, and at the same time promotes the directional arrangement of the lamellar MAX phase in the Ag matrix, obtaining a dense and anisotropic Ag / MAX material. This research demonstrates the improvement of material properties by directional arrangement, especially in improving the arc erosion resistance of the material. However, this method relies on empirical parameters to control the plastic deformation process, which makes the research and development cycle longer. At the same time, since Ag is a precious metal, the trial-and-error cost of products is relatively high.
[0004] The three-dimensional processing diagram can effectively reveal the influence of deformation temperature, strain, and strain rate on the workability of material plastic deformation, providing an important basis for the process design and optimization of materials at medium and high temperatures. Patent CN117789871A discloses a method for optimizing the medium and high temperature controlled rolling parameters of a marine high-magnesium aluminum alloy, realizing the process design and optimization of medium and high temperature controlled rolling through a three-dimensional processing diagram. However, the existing research on hot processing diagrams mainly focuses on the processing technology and mechanical property optimization of structural materials such as magnesium aluminum alloys and steels. Compared with structural materials, the improvement of electrical properties also needs to be considered during the processing of electrical contact materials. For particle-reinforced electrical contact materials, such materials are prone to obtaining high mechanical properties during the dynamic recrystallization process, but the influence of different softening mechanisms such as dynamic recovery and dynamic recrystallization during the processing on the reinforcing phase particles does not necessarily develop the electrical properties of the material in a beneficial direction. Summary of the Invention
[0005] The purpose of the present invention is to overcome the above-mentioned shortcomings and deficiencies of the existing technology. By simulating the stress-strain state and microstructure evolution during processing with Gleeble, a method for optimizing the plastic deformation parameters of Ag / MAX electrical contact materials is provided. It avoids relying on empirical parameters for long-term experiments and material waste, and can avoid dangerous processing areas during the plastic deformation process. The present invention divides the safe area and instability area of the material during the plastic deformation process through a three-dimensional processing diagram. Combining the work hardening curve, the safe area can be directly subdivided into the dynamic recovery and dynamic recrystallization regions without microscopic structure observation, reducing the experimental process and saving costs.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for optimizing the plastic deformation parameters of Ag / MAX electrical contact materials. It includes the following steps:
[0008] S1: Process the Ag / MAX sample into a cylindrical or cuboid hot compression specimen;
[0009] S2: Use a Gleeble-3500 thermal simulation testing machine to conduct thermal simulation compression experiments on the hot compression specimen. Add lubricant between the sample and the base, and set the deformation temperature, strain rate, and deformation amount;
[0010] S3: Draw the true stress-true strain curve of the specimen according to the flow stress at different deformation temperatures and strain rates, obtain the stress values corresponding to different strains, deformation temperatures, and strain rates, and calculate and obtain the strain rate sensitivity index, power dissipation coefficient, material flow instability parameter, and work hardening rate;
[0011] S4: Draw the work hardening curve of the work hardening rate and strain, and judge the softening mechanism region during the plastic deformation process of the material;
[0012] S5: Construct a power dissipation map based on the dynamic material model and a plastic instability map based on the plastic instability judgment criterion; superimpose the power dissipation map and the plastic instability map to obtain a hot processing map, and divide the safe zone and the instability zone; make hot processing maps under different strains, and then draw a three-dimensional hot processing map including strain changes;
[0013] S6: Different plastic deformation processes correspond to different strains. According to the safe zones under different strains in the three-dimensional hot processing map, combined with the work hardening curve, select the temperature and strain rate for the plastic forming of Ag / MAX, determine the process parameters during the plastic deformation, and obtain the Ag / MAX electrical contact material that meets the performance requirements.
[0014] As one of the preferred solutions of the above technical solution, in step S1, in the Ag / MAX electrical contact material, the mass of the MAX phase accounts for 10 - 20% of the total mass. The types of the MAX phase include but are not limited to Ti 3 AlC 2 、Ti 2 AlC and Ti 3 SiC 2 etc.
[0015] As one of the preferred solutions of the above technical solution, in step S2, the thermal simulation compression experiment is as follows: heat the thermal compression specimen to the deformation temperature at a heating rate of 5 - 30 °C / s, hold for 5 - 30 min, then conduct a thermal compression experiment at the strain rate, and cool with water, and the engineering strain is 50% - 80%.
[0016] As one of the preferred solutions of the above technical solution, in step S2, the deformation temperature is 200 - 900 °C, the selected temperature interval is 20 - 100 °C, and the strain rate is 10 -3 -30 s -1 .
[0017] As one of the preferred solutions of the above technical solution, in step S3, the expressions of the strain rate sensitivity index, power dissipation coefficient, material rheological instability parameter, and work hardening rate are respectively:
[0018]
[0019]
[0020] Among them, σ is the true stress (MPa) of the material at different strain rates and temperatures; is the strain rate (s -1 ); m is the strain rate sensitivity index, η is the power dissipation coefficient, ξ is the material rheological instability parameter, and θ is the work hardening rate of the material.
[0021] As one of the preferred solutions of the above technical solution, in step S4, the work hardening curve There are three cases: when the work hardening rate θ drops below zero and remains near zero, it indicates that dynamic recovery and work hardening are in balance, and softening is dominated by dynamic recovery; when the work hardening rate θ remains higher than zero, work hardening dominates plastic deformation; if the work hardening rate drops below zero, reaches the minimum value and then returns to zero, softening is dominated by dynamic recrystallization.
[0022] As one of the preferred solutions of the above technical solution, in step S5, a power dissipation diagram is constructed with η varying with temperature and strain rate, and the parameter ξ is plotted as a function of temperature and strain rate. The region where ξ < 0 is the rheological instability region, forming a rheological instability diagram.
[0023] As one of the preferred solutions of the above technical solution, in step S6, process parameters in different plastic deformation processes can obtain materials that meet different performance requirements. The dynamic recovery region can obtain stronger electrical conductivity and arc erosion resistance, while the dynamic recrystallization region can obtain stronger strength and plasticity. According to the safe regions at different strains in the three-dimensional hot processing diagram, combined with the work hardening curve, the dynamic recovery-dominated region and the dynamic recrystallization-dominated region are divided; the temperature and strain rate of plastic forming are selected according to the required material properties.
[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0025] (1) The present invention studies the plastic deformation behavior of Ag / MAX electrical contact materials through thermal simulation experiments, constructs the three-dimensional processing diagram of the material, and specifically divides the hot deformation region in combination with the work hardening curve. This method can more accurately reflect the actual behavior of the material at different temperatures and strain rates, clearly distinguish the dynamic recrystallization region and the dynamic recovery region, optimize the deformation parameters, provide a theoretical basis for the plastic deformation process in actual production, and improve the production controllability and consistency of the material.
[0026] (2) The method of the present invention can flexibly select the deformation temperature and strain rate according to the actual situation, so it can simulate all working conditions in the production process of Ag / MAX electrical contact materials, and has universality; at the same time, the method of the present invention is not limited to Ag / MAX composite materials, and can also be applied to other Ag-based electrical contact materials.
[0027] (3) The method of the present invention constructs a work hardening curve to first judge the softening mechanism of the material and narrow the selection parameter range of the processing diagram. In addition, by optimizing the plastic deformation parameters, the uncertainty brought by empirical control is reduced, thereby reducing the trial-and-error cost and shortening the R & D cycle, promoting the industrial application of Ag / MAX composite materials, especially in the production process of precious metal materials, significantly reducing the production cost.
[0028] (4) By means of deformation processes in different regions to meet different usage requirements and application environments. Improve the microstructure of the material (such as the oriented arrangement of MAX phases), enhance the arc erosion resistance, or refine the matrix grains to improve the plasticity and strength of the material. The present invention is directed to particle-reinforced electrical contact materials, taking into account the dual optimization of mechanical and electrical properties. During processing in the safety region, in addition to changes in mechanical properties, attention should also be paid to changes in electrical conductivity and arc erosion resistance, etc. This is related to the distribution and orientation of the reinforcing phase in the matrix. When the material is processed in the dynamic recrystallization region, the plasticity and toughness can be improved due to the refinement of the matrix grains, but the distribution of the reinforcing phase will result in lower relevant electrical properties compared to the material processed in the dynamic recovery region. Correspondingly, processing in the dynamic recovery region is conducive to improving the degree of oriented arrangement of the reinforcing phase and improving the electrical properties of the material, but the mechanical properties cannot reach the most excellent state. Therefore, in practical applications, the most suitable processing region can be selected according to specific usage requirements and application environments. Description of the Drawings
[0029] Figure 1 is the true stress-true strain curve.
[0030] Figure 2 is the work hardening curve.
[0031] Figure 3 is the hot processing map at a true strain of 0.6.
[0032] Figure 4 are the micrographs of (a) the dynamic recovery-dominated region and (b) the dynamic recrystallization-dominated region corresponding to a true strain of 0.6.
[0033] Figure 5 are the three-dimensional hot processing maps at different strains. Detailed Embodiments
[0034] The technical solution of the present invention is further described below. The following description is only for understanding the technical solution of the present invention and is not used to limit the scope of the present invention. The protection scope of the present invention is subject to the claims.
[0035] The present invention provides a method for optimizing the plastic deformation parameters of an Ag / MAX electrical contact material, which is applied to the compression experiment of Ag / Ti 3 AlC 2 and is reasonably improved according to the temperature, strain rate set in the Gleeble compression test and the corresponding microstructure.
[0036] Taking the Ag-10wt.%Ti 3 AlC 2 electrical contact material as an example. The specific steps are as follows:
[0037] (1) Prepare the prepared Ag / Ti 3 AlC 2 Wire cut into cylindrical specimens with Φ6mm×h 9mm, and use a Gleeble-3500 thermal simulation test machine to conduct thermal simulation compression experiments on the hot compression specimens. Set the deformation temperatures to 400°C, 500°C, and 600°C respectively, and the strain rate to 10 -3 s -1 、10 -2 s -1 and 10 -1 s -1 , and the engineering strain is 50%;
[0038] (2) Draw the true stress-true strain curve of the specimen according to the flow stress obtained from the above deformation temperature and strain rate. Take the curve with a true strain of 0.6 as an example, such as Figure 1 . Obtain the stress values corresponding to different strains, deformation temperatures, and strain rates, calculate and obtain the strain rate sensitivity index, power dissipation coefficient, and material flow instability parameter. The expressions of each parameter are as follows:
[0039]
[0040] Among them, σ is the true stress (MPa) of the material at different strain rates and temperatures; is the strain rate (s -1 ); m is the strain rate sensitivity index, η is the power dissipation coefficient, and ξ is the material flow instability parameter. Take the sample with a true strain of 0.6 as an example, as shown in Table 1;
[0041] Table 1
[0042]
[0043] (3) Differentiate the true stress-true strain curves at different temperatures and strain rates to obtain the work hardening rate Draw the work hardening curve Take the sample with a true strain of 0.6 and a strain rate of 0.001s -1 as an example, such as Figure 2 . Figure 2 Among them, the softening at 400°C is mainly dominated by dynamic recovery, and the softening at 500-600°C is mainly dominated by dynamic recrystallization. Drawing the work hardening curves at different strain rates and temperatures can roughly divide different softening mechanism regions.
[0044] (4) Matrixize the strain rate and deformation temperature data matrices respectively to construct a power dissipation diagram based on the dynamic material model and a plastic instability diagram based on the plastic instability judgment criterion. The rheological instability behavior can be quantitatively characterized according to the plastic instability criterion. When the material is in the safe region, the material realizes grain refinement through dynamic recrystallization, completes dislocation rearrangement by means of dynamic recovery, and may undergo superplastic flow dominated by grain boundary slip. These coordinated deformation mechanisms effectively maintain the uniform plasticity of the material. On the contrary, when the material is in the critical negative value range, its rheological stability is significantly reduced. At this time, the microstructure evolution presents typical instability characteristics: adiabatic shear bands are generated under the thermo-mechanical coupling effect, and significant localized deformation phenomena occur. Superimpose the power dissipation diagram and the plastic instability diagram to obtain the processing map of Ag / Ti 3 AlC 2 at the set temperature, and the safe area and instability area can be divided. Take the sample with a true strain of 0.6 as an example, Figure 3 the shaded part in it is the instability area, and the white part is the safe area. According to the work hardening curve, different softening mechanism areas in the figure are given to judge the dynamic recovery-dominated area and the dynamic recrystallization-dominated area in the safe area. As Figure 4 shows, the microstructural diagrams corresponding to (a) the dynamic recovery-dominated area and (b) the dynamic recrystallization-dominated area respectively. In the dynamic recovery area (such as 400 °C, 0.01 s -1 ), the directional arrangement of the reinforcement phase is more obvious, and stronger electrical conductivity and arc erosion resistance can be obtained. In the dynamic recrystallization area (such as 600 °C, 0.1 s -1 ), the degree of particle directional arrangement is significantly weakened, the distribution density of the reinforcement phase is high, the tortuosity degree of the conduction path is high, and the electrical conductivity of the material is weaker than that in the dynamic recovery area. However, due to dynamic recrystallization, the strength and plasticity of the matrix are improved.
[0045] (5) Make the hot processing maps at different strains and combine them into a three-dimensional hot processing map including strain changes, as Figure 5 shown. In the figure, the instability area mainly concentrates in the high strain rate region at different strains. As the true strain increases to 0.6, the instability area in the high temperature and high strain rate part disappears. The main safe areas at different strains are shown in Table 2. It should be noted that when the deformation temperature is 400 - 500 °C and the strain rate is 0.001 - 0.01 s -1 , the processing maps are all in the safe deformation area. Combining the work hardening curves under different parameters, the deformation areas of Ag / Ti 3 AlC 2 with different performance requirements can be selected.
[0046] Table 2
[0047] Strain Safe processing area 0.1 <![CDATA[400 - 600 °C, 0.001 - 0.01 s -1 > 0.3 <![CDATA[400 - 520 °C, 0.001 - 0.01 s -1 ; 520 - 600 °C, 0.001 - 0.1 s -1 > 0.5 <![CDATA[400 - 470 °C, 0.001 - 0.01 s -1 ; 470 - 600 °C, 0.001 - 1 s -1 > 0.6 <![CDATA[400 - 470 °C, 0.001 - 0.01 s -1 ; 470 - 600 °C, 0.001 - 1 s -1 >
[0048] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A method for optimizing the plastic deformation parameters of Ag / MAX electrical contact materials, characterized in that The following steps are involved: S1: Process the Ag / MAX sample into a cylindrical or rectangular hot compression specimen; S2: Use a thermal simulation test machine to perform a thermal simulation compression test on the thermal compression specimen, and set the deformation temperature, strain rate, and deformation amount; S3: Draw the true stress-true strain curve of the sample according to the rheological pressure at different deformation temperatures and strain rates, obtain the stress values corresponding to different strains, deformation temperatures, and strain rates, and calculate and find the strain rate sensitivity index, power dissipation coefficient, and material rheological instability parameters; S4: Calculate the work hardening rate of the material and draw a work hardening curve of the relationship between the work hardening rate and strain to determine the softening mechanism area during the plastic deformation process of the material; S5: Construct a power dissipation diagram based on a dynamic material model and a plastic instability diagram based on the plastic instability judgment criterion; superimpose the power dissipation diagram and the plastic instability diagram to obtain a thermal processing diagram, and divide the safe area and the instability area; make thermal processing diagrams under different strains, and then draw a three-dimensional thermal processing diagram including strain changes; S6: According to the safety zone under different strains in the three-dimensional thermal processing diagram, the temperature and strain rate of plastic forming are selected in combination with the work hardening curve, and the process parameters during the plastic deformation process are determined to obtain Ag / MAX electrical contact materials that meet the performance requirements.
2. The method for optimizing plastic deformation parameters of Ag / MAX electrical contact materials according to claim 1, characterized in that: In step S1, the mass of the MAX phase in the Ag / MAX electrical contact material accounts for 10-20% of the total mass; the types of MAX phase include but are not limited to Ti3AlC2, Ti2AlC and Ti3SiC2.
3. The method for optimizing plastic deformation parameters of Ag / MAX electrical contact materials according to claim 1, characterized in that: In step S2, the deformation temperature is 200-800°C and the strain rate is 10 -3 -10s -1 , the deformation is 50%-80%.
4. The method for optimizing plastic deformation parameters of Ag / MAX electrical contact materials according to claim 1, characterized in that: In step S2, the thermal simulation compression test is: heating the thermal compression sample to the deformation temperature at a heating rate of 5-30°C / s, keeping the temperature for 5-30 minutes, and then performing a thermal compression test at the strain rate, and water cooling.
5. The method for optimizing plastic deformation parameters of Ag / MAX electrical contact materials according to claim 1, characterized in that: The expressions of strain rate sensitivity index, power dissipation coefficient, material rheological instability parameter and work hardening rate are: Where, σ is the true stress of the material at different strain rates and temperatures (MPa); is the strain rate (s -1 ), m is the strain rate sensitivity index, η is the power dissipation coefficient, ξ is the material rheological instability parameter, the area where ξ<0 is the rheological instability zone, and θ is the work hardening rate of the material.
6. The method for optimizing plastic deformation parameters of Ag / MAX electrical contact materials according to claim 1, characterized in that: Work hardening curve in step S4 There are three situations: when the work hardening rate θ drops below zero and then remains near zero, it indicates that dynamic recovery and work hardening are balanced, and softening is dominated by dynamic recovery; when the work hardening rate θ remains above zero, work hardening dominates plastic deformation; if the work hardening rate drops below zero, reaches the minimum value and then returns to zero, softening is dominated by dynamic recrystallization.
7. The method for optimizing plastic deformation parameters of Ag / MAX electrical contact materials according to claim 1, characterized in that: In step S5, the power dissipation coefficient varies with the strain rate and temperature to draw a power dissipation diagram, and the material rheological instability parameter varies with the strain rate and temperature to draw a plastic instability diagram.
8. The method for optimizing plastic deformation parameters of Ag / MAX electrical contact materials according to claim 1, characterized in that: In step S6, the dynamic recovery dominant zone and the dynamic recrystallization dominant zone are divided according to the safe zones under different strains in the three-dimensional thermal processing diagram in combination with the work hardening curve; the temperature and strain rate of plastic forming are selected according to the material performance requirements.
Citation Information
Patent Citations
Preparation method of Ag / MAX electric contact material
CN109852837A
Medium-high temperature control rolling parameter optimization method for marine high-magnesium aluminum alloy
CN117789871A